(untitled) (The Science Post, 2025)
Coronary Heart Disease (CHD) remains the leading global cause of death, representing a persistent challenge in modern healthcare. Early detection is crucial for reducing mortality and improving treatment outcomes. Over the past two decades, diagnostic technologies for CHD have progressed dramatically—from traditional tools like electrocardiograms (ECG) and treadmill stress testing to advanced imaging methods such as Cardiac Magnetic Resonance Imaging (CMR) and Computed Tomography Coronary Angiography (CTCA), as well as biomarker analysis and wearable biosensors. This paper provides a theoretical exploration of how these technologies have evolved, the factors that have driven their clinical adoption, and the emerging trends that define the future of cardiac diagnostics. Drawing on empirical patterns and conceptual frameworks, the discussion emphasizes diagnostic accuracy, non-invasiveness, patient accessibility, and digital integration. The study concludes with a forward-looking assessment of potential barriers, including ethical challenges, cost disparities, and infrastructural limitations, advocating for equitable implementation and multidisciplinary collaboration to fully harness diagnostic innovations for global cardiac care.